NA62 Charged Particle Hodoscope. Design and performance in 2016 run. (27th June 2017) - Kholodenko, S.
Abstract: The NA62 experiment at CERN SPS aims to measure the branching ratio of the ultra-rare decay K +  → π + νν̄ with 10% accuracy. The experiment operates with a 75 GeV/c high intensity (750 MHz) secondary beam. A new detector, named Charged Particle Hodoscope (CHOD), designed to produce an input signal to the L0 trigger processor for events with charged particles produced in kaon decays, has been assembled, installed, integrated into NA62 Data Acquisition System (DAQ) and commissioned in 2016. During the whole 2016 run the detector has been in continuous operation. Design and performance features of the detector are presented.